Kavel's people : their story of migration from Prussia to South Australia for the sake of their faith, and their initial settlement, told mainly from journals, letters, and other documents of the time - Schubert, David A. (David Arthur), 1942- (Adelaide : Lutheran Publishing House, 1985)
Occasional references to Aboriginal people and to the Aborigines Protection Society.
Ill. on lining papers.
Includes index.
Bibliography: p. 179-182.
Keywords: Prussians (Baltic people) -- South Australia -- History; History - Biographies - Non-Indigenous.; Religions - Christianity - Lutheran Church; Settlement and contacts - Germans; Settlement and contacts - Ethnic groups, immigration and multiculturalism; South Australia -- Emigration and immigration -- History; South East South Australia (SE SA SI54, SJ54); Barossa (SE SA SI54-09)